Applying Workload and Full-Time Equivalent Analysis to Determine Optimal Teacher Requirements - Ginting, Gresia Vani Br; Sayekti, Andita (Universitas Pakuan, 2025)
This study aims to analyze teacher workload as a basis for determining the optimal number of teaching staff at SMA Negeri 1 Berastagi. Human resource management plays a critical role in ensuring the efficiency and sustainability of educational institutions. The research applies the workload analysis and Full-Time Equivalent (FTE) method, following the guidelines of the Indonesian Ministry of Administrative and Bureaucratic Reform Regulation (Permenpan RB) No. 1 of 2020. Using a saturated sampling method, the study involves all 48 civil servant teachers across various subject areas, including mathematics, science, social studies, languages, and general education. The findings reveal disparities in workload distribution, where several teachers experience overload and others underload conditions. These imbalances suggest the need for strategic adjustments, such as adding teachers in physics, chemistry, geography, and economics, while reducing honorary staff in subjects like religion and physical education. The managerial implications highlight the importance of applying the POAC management functions planning, organizing, actuating, and controlling—to achieve workload balance, optimize staffing, and enhance organizational effectiveness. Overall, workload-based human resource planning is essential for improving teacher efficiency and maintaining educational quality.